Membrane bioreactor for treatment of high-sulfate wastewater - 222930 Dewi Dwirianti Hadiwinoto (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Master of Engineering (Environmental)) - Universiti Teknologi Malaysia, 2002